Multimodal Transport Operator Liability Insurance Model - Zelenika, Ratko; Lotrič, Tomaž; Bužan, Ervin (Promet - Traffic&Transportation, 2012)
Multimodal transportation means transporting goods from a pickup point, where the operator receives the goods, all the way to the delivery location, using at least two different means of transportation, covered under the same multimodal transport contract and by only one document, regardless of the number or type of transportation vehicles used. The key factor to the optimal operation of multimodal transportation is the multimodal transport operator. It is up to this individual to compensate for various unpredictable circumstances, the complexity of the business processes, nature’s whims and carelessness. He must also organize and execute multimodal transport in all stages. Due to the above mentioned dangers and the fact that the area of liability insurance for multimodal transport operators is still being neglected, this article raises some valid points in favour of a proposal that would cover all of the transportation means as well as all the accompanying activities with a single insurance policy. The model includes 17 elements of liability insurance for a multimodal transport operator and all values which quantify the insurance elements in 2009 as well as the projected values for 2015, when progress is expected in the areas pertaining to the implementation of economical processes concerning transit development, as well as values for 2025, representing a period of innovation, reconstruction, optimization and modernization. With this supposed model for liability insurance of a multimodal transport operator, the foundation is laid for a liability insurance which would be used by a multimodal transport operator. KEYWORDS: transport insurance, multimodal transport, multimodal transport operator, multimodal transport operator liability systems